2008
DOI: 10.1093/humrep/den028
|View full text |Cite
|
Sign up to set email alerts
|

The presence of heparan sulfate in the mammalian oocyte provides a clue to human sperm nuclear decondensation in vivo

Abstract: The results presented in this paper demonstrate for the first time that HS is present in the mammalian oocyte and show that HS is necessary for fresh oocytes to express their sperm decondensing ability in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 29 publications
4
16
0
2
Order By: Relevance
“…To date, the nature of the molecule required for the process of protamine replacement by oocyte-derived histone was still unknown. Some previous studies have reported that HS in concert with GSH leads to SCD induction in human spermatozoa [22,28,47]. The results of the present study are in line with these previous studies, demonstrating that HS was expressed in the mouse ooplasm and induced chromatin accessibility during SCD.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…To date, the nature of the molecule required for the process of protamine replacement by oocyte-derived histone was still unknown. Some previous studies have reported that HS in concert with GSH leads to SCD induction in human spermatozoa [22,28,47]. The results of the present study are in line with these previous studies, demonstrating that HS was expressed in the mouse ooplasm and induced chromatin accessibility during SCD.…”
Section: Discussionsupporting
confidence: 93%
“…Heparin, a negatively charged compound, is made by secretory granules of mast cells, whereas no heparin is found in cumulus-oocyte complexes (COCs) and granulosa cells. In contrast, HS, a negatively charged polysaccharide with a qualitatively similar function and structure to heparin, is produced in all types of cells, including oocytes [21,22]. We also found that HS has the ability to decondense sperm chromatin.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…This is consistent with and is likely facilitated by the GAGs, including heparin, in mammalian oocytes [Reyes et al 2004;Romanato et al 2008]. In this study we showed that histone H1 is present in the bull sperm nucleus and is released during nuclear decondensation mediated by the heparin-GSH.…”
Section: Discussionsupporting
confidence: 87%
“…В сперме плотная упаковка хроматина обеспечивается протаминами, а не гистонами. После оплодотворения ГС облегчают удаление протаминов, что способствует деконденсации хроматина сперматозоида и слиянию муж ского и жен-ского генетического материала [125]. ДС и гепарин также способствовали деконденсации хроматина в мы-шиных сперматозоидах in vitro, но активность гепари-на при этом была значительно выше.…”
Section: функциональная роль внутриядерных протеогликановunclassified